CAPITAL STRUCTURE, FIRM SIZE, AND EFFECTIVE TAX RATE ON THE FINANCIAL PERFORMANCE OF AUTOMOTIVE SUBSECTOR COMPANIES - Nurasik; Ningdiyah, Endra Wahyu; Abidin, Fitiyan Izzah Noor (Journal of Economic and Economic Policy, 2024)
General Background: Financial performance is a crucial indicator of a company's success and sustainability, particularly in competitive industries such as the automotive subsector. Various factors, including capital structure, firm size, and effective tax rate, are considered significant determinants of financial performance. Specific Background: In the context of the automotive subsector, these factors have garnered considerable attention due to the industry's capital-intensive nature and its exposure to dynamic market conditions. However, existing research often overlooks the combined impact of these variables within this specific sector. Knowledge Gap: Limited studies have comprehensively examined the influence of capital structure, firm size, and effective tax rate on the financial performance of automotive subsector companies, particularly during the period 2020-2023, characterized by global economic uncertainty. Aims: This study aims to analyze the effects of capital structure, firm size, and effective tax rate on the financial performance of automotive subsector companies in Indonesia. Results: Using a quantitative approach and multiple linear regression analysis on data from 12 purposively sampled companies during the 2020-2023 period, the findings reveal that all three variables—capital structure, firm size, and effective tax rate—significantly influence financial performance. Novelty: The study provides fresh insights into the interrelation of these financial determinants within the automotive subsector, highlighting their unique impact during a period of global economic flux. Implications: These findings offer valuable implications for corporate management and policymakers in designing strategies to enhance financial performance, emphasizing the need for optimal capital structuring, scaling strategies, and effective tax planning. Further research could explore longitudinal impacts and sectoral comparisons to deepen understanding of these dynamics.